The Potential of Black Pepper Farmer Groups: One of The Strategic Policies in Strengthening Farmer Groups - Berliana, Dayang; Sutarni, Sutarni; Sudiyo, Sudiyo; Indaryati, Sri (Universitas Negeri Gorontalo, 2024)
One spice that has many functions and benefits is pepper. Pepper is widely cultivated by farmers involved in farmer groups. The role of farmer groups as institutions is able to coordinate the marketing of black pepper so as to improve the bargaining position of farmers. The aims of this study were to the potential of black pepper farmer groups in East Lampung. To obtain the necessary data, this research uses a survey method. The data used in this research are primary and secondary data, which are then processed using qualitative methods. The main data was collected through direct observation at the research location as well as in-depth interviews with 21 administrators and members of the Sido Makmur farmer group, which were conducted using questionnaires from June to October 2022. Data analysis to answer the objectives using qualitative descriptive analysis To analyze problems and analysis potentials faced by farmer groups in increasing market expansion using qualitative descriptive analysis and Focus Discussion Groups (FGD) in order to find internal factors (strengths and weaknesses) and external factors (opportunities and challenges) faced by farmer groups Sido Makmur in increasing the expansion of the black pepper market. The characteristics of farmers include the average age of productive age, the average level of formal education of junior and senior high school graduates, the average area of land cultivated by farmers is above 1 ha, as well as internal and external factors as strategic analysis variables (internal factors: farmer's social capital consists of social networks and good trust, institutions, sufficient group capacity, group characteristics in the form of capital, profits, and limited resources, and external factors: External Factors Policy, where several stakeholders have been assisted in the transfer of science and technology).